Empowering Karangjati Village MSMEs through cost of goods sold calculation and digital marketing facilitation - Muhdiyanto, Muhdiyanto; Yuliani, Nur Laila; Darmadi, Ravindra Ardiana (Community Empowerment, 2025)
PAGUPON, a community group in Karangjati Village, provides education and training to micro, small, and medium enterprises (MSMEs) to support the Borobudur Special Economic Zone. As the number of businesses under its guidance increased, PAGUPON faced challenges in managing finances and marketing. This community service aimed to assist PAGUPON in providing financial management and digital marketing training to its MSMEs. After the training and mentorship, the MSMEs were able to determine their product costs and expand their market reach through Instagram and Facebook.